EKSPLORASI FAKTOR KUNCI MINAT INVESTASI MELALUI APLIKASI BERBASIS MOBILE (Studi Pada Generasi Z) - Azzahra Rahmi Nurfadhila; Akhmad Saebani (Bajang Institute, 2024)
Generation Z (Gen Z) is a generation that grew up in the era of rapidly developing digital technology and the internet, making them very familiar with technology, social media and information that can be accessed instantly. Gen Z wants solutions that are practical and easy to use. Online investment platforms such as mobile trading applications or other peer-to-peer services make it easy to start investing with just a few clicks on your mobile phone. Gen Z can access the stock market, mutual funds, crypto, or other alternative investments with relatively low initial capital. This research aims to analyze interest in mobile application-based investments by Gen Z. The Theory of Planned Behavior assumes that a person's behavior will be in line with their conscious intentions. This research is quantitative research with primary data using questionnaires and Likert scales for measurement. The population is beginner investors from Generation Z with data collected and data collection using accidental sampling techniques. The sample obtained in this research amounted to 95 respondents. The method used is Structural Equation Model (SEM). The results of this research show that Gen Z's interest in investing via mobile applications is significantly influenced by the Digital Financial Literacy variable and the Information Quality variable, while the Mobile-based investment application System Security variable does not statistically influence Gen Z's interest in investing via mobile applications. Overall, the availability of online investment apps provides an easy and affordable opportunity for Gen Z to start their financial journey. With technology continuing to develop, investments are becoming more inclusive, transparent, and applications with gamification formats are becoming relevant for Gen Z's digital lifestyle